Thermal and hydraulic characteristics of nanofluid in a triangular grooved microchannel heat sink (TGMCHS) - Kuppusamy N.R.; Mohammed H.A.; Lim C.W. (Elsevier Inc., 2023)
A numerical simulation is conducted to examine the heat transfer and fluid flow characteristics of nanofluids in a triangular grooved microchannel heat sink (TGMCHS). The governing and energy equations are solved using the finite volume method (FVM). The influence of the geometrical parameters such as the angle (50-100°), depth (10-25 ?m) and pitch (400-550 ?m) of the groove on the thermal performance of TGMCHS was examined. The effects of different nanoparticle types (Al2O3, CuO, SiO2, ZnO), volume fraction (? = 0.01-? = 0.04), particle diameter (25-80 nm) and base fluid (water, ethylene glycol, engine oil) at different Reynolds numbers are also studied. The thermal performance of TGMCHS had significant increment with the increment of angle and depth of the groove accompanied with an optimum groove pitch. It is found that the TGMCHS thermal performance of using Al2O3-H2O (? = 0.04, d np = 25 nm) is outperformed the simple MCHS using water. © 2014 Elsevier Inc. All rights reserved.